2023
DOI: 10.3390/jfmk8040150
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Protective Measures and Rules in Reducing the Incidence of Injuries in Combat Sports: A Scoping Review

Rastislav Štyriak,
Radovan Hadža,
Rafael Arriaza
et al.

Abstract: In recent years, much effort has been made to reduce the injury rate in combat sports. However, the question remains to what extent these measures are effective. Analysis of studies could provide evidence of the effectiveness of measures aimed at reducing the incidence of injuries. This scoping review aims (1) to map research articles dealing with the effectiveness of proper use of protective measures in reducing the incidence of injuries in combat sports; (2) to investigate to what extent the proper use of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This finding is consistent with studies that have identified these activities as common causes of facial trauma in younger demographics [ 4 ]. Research has further emphasized the need for targeted preventive measures, such as the use of protective gear in sports and safe driving campaigns, to reduce the incidence of facial fractures in younger populations [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with studies that have identified these activities as common causes of facial trauma in younger demographics [ 4 ]. Research has further emphasized the need for targeted preventive measures, such as the use of protective gear in sports and safe driving campaigns, to reduce the incidence of facial fractures in younger populations [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One effective measure that is widely recommended is the use of gear like mouth guards and helmets. A study has shown that fitted mouth guards are particularly effective in reducing the occurrence and severity of injuries among young athletes involved in various sports (8)(9)(10). Additionally, certain sports have implemented rule modifications to minimize the risk of injuries.…”
Section: Introductionmentioning
confidence: 99%